In vitro simulation of immuno-suppression caused by Trypanosoma brucei: Active involvement of gamma interferon and tumor necrosis factor in the pathway of suppression - Darji, A.; Beschin, A.; Sileghem, M.R.; Heremans, H.; Brys, L.; Baetselier, P. de (1996)
Experimental infections of mice with the African trypanosome Trypanosoma brucei lead to a profound state of T-cell unresponsiveness in the lymph node cell (LNC) compartment. This suppression is mediated by macrophage-like cells which inhibit interleukin 2 (IL-2) secretion and down-regulate IL-2 receptor expression (M. Sileghem, A. Darji, R. Hamers, M. Van de Winkel, and De Baetselier, Eur. J. Immunol. 19:829- 835, 1989). Similar suppressive cells can be generated in vitro by pulsing 2C11-12 macrophage hybridoma cells with opsonized T. brucei parasites (2C11-12P cells). Cocultures of 2C11-12P cells and LNCs secrete higher levels of gamma interferon (IFN-gamma), and the hyperproduction of IFN-gamma was found to be confined to CD8+ lymphoid cells. Elimination of CD8+ cells from cocultures of 2C11-12P cells and LNCs restores the T-cell proliferative response. Furthermore, addition of neutralizing anti-IFN-gamma antibodies to the cocultures reduces the level of suppression and concomitantly restores the level of IL-2 receptor expression. Hence, IFN-gamma plays a cardinal role in this in vitro model for T. brucei-elicited immunosuppression. Cocultures of LNCs and 2C11-12P cells in a two-chamber culture system further demonstrated that cell-cell contact is required for hyperproduction of IFN-gamma and, moreover, that IFN-gamma cooperates with a 2C11-12P- derived diffusible factor to exert its suppressive activity. Finally, tumor necrosis factor alpha (TNF-alpha produced by 2C11-12P cells was found to be implicated in the hyperproduction of IFN-gamma, since addition of neutralizing anti-TNF-alpha antibodies to cocultures reduced the level of suppression and concomitantly abrogated the hyperproduction of IFN-gamma. Collectively, our findings indicate that T. brucei-elicited suppressive 2C11-12 macrophage cells differentially influence T-cell subpopulations: (i) CD8+ cells are signaled via cell- cell contact to produce IFN-gamma, and TNF-alpha is implicated in this process, and (ii) locally produced IFN-gamma and macrophage-released factors act in concert to inhibit CD4+ and CD8+ T-cell proliferative responses.